2007
DOI: 10.1111/j.1745-7254.2007.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GSM 1800 MHz on dendritic development of cultured hippo-campal neurons

Abstract: Aim: To evaluate the effects of global system for mobile communications (GSM) 1800 MHz microwaves on dendritic filopodia, dendritic arborization, and spine maturation during development in cultured hippocampal neurons in rats. Methods: The cultured hippocampal neurons were exposed to GSM 1800 MHz microwaves with 2.4 and 0.8 W/kg, respectively, for 15 min each day from 6 days in vitro (DIV6) to DIV14. The subtle structures of dendrites were displayed by transfection with farnesylated enhanced green fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…There are evidences that microwaves may produce adverse biological effects on the nervous system (Campisi et al, 2010;Dasdag et al, 2009;Ning et al, 2007;Orendácová et al, 2007). Moreover, Panagopoulos (2011) emphasized that cells are metabolically active (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…There are evidences that microwaves may produce adverse biological effects on the nervous system (Campisi et al, 2010;Dasdag et al, 2009;Ning et al, 2007;Orendácová et al, 2007). Moreover, Panagopoulos (2011) emphasized that cells are metabolically active (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous work indicated that the probes containing (rR) 3 R 2 can efficiently enter the cytosol of live cells not via endocytosis but through direct penetration, and a 30 min incubation with the cells in a 5% CO 2 atmosphere at 37 °C is sufficient for the probes to bind to their targets efficiently, so we followed this experimental process. Based on the results, we first investigated the cell permeability and specificity of Lifeact‐AF647‐CPP by co‐localization study with GFP–actin in live BSC‐1 cells. The results indicate that the probe Lifeact‐AF647‐CPP successfully entered the live cells and co‐localized with the GFP–actin (Pearson's coefficient: 0.746; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After staining with Lifeact‐Atto488‐CPP or Lifeact‐Atto565‐CPP, F‐actin in live U2OS cells was characterized clearly in SIM images, with an evident improvement in resolution (mean values of 84.12 and 98.66 nm) in contrast with the wide‐field images (Figs (a), (b), (g) and (h)). As contrasts, we also expressed the GFP–actin and EGFP‐Lifeact or labeled F‐actin with a commercially available probe SiR–actin in live U2OS cells before SIM imaging. The images of GFP–actin were too blurry to distinguish F‐actin from the background in the cytosol (Figs (c) and (d)).…”
Section: Resultsmentioning
confidence: 99%
“…The care and use of animals in these experiments followed the guidelines and protocol approved by the care and use of animals committee of the Chinese academy of sciences. Primary cultures of hippocampal neurons were prepared from postnatal one‐day‐old Sprague‐Dawley rats as previously reported (Luo et al, 2002; Ning et al, 2007). Briefly, after careful dissection from diencephalic structures, the hippocampi were chopped and then digested in 0.25% trypsin for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, half of the medium was replaced twice a week with Neurobasal medium containing 2% B27 supplement, 1% antibiotic, and 2 mM glutamine. Hippocampal neurons were routinely transfected with F‐GFP (3 μg/dish) by Lipofectamine 2000 (Invitrogen) at DIV5 (Ning et al, 2007). For dendritic branch imaging, hippocampal neurons were treated with IL‐2 at 1, 10, or 100 ng/mL for 48 hr before image acquisition for dose‐dependent analysis and were treated with 10 ng/mL IL‐2 for 24, 48, or 72 hr before image acquisition for time‐dependent analysis.…”
Section: Methodsmentioning
confidence: 99%